A mixed‐methods evaluation of continuous electronic fetal monitoring for an extended period. (27th September 2018) - Crawford, Alexandra; Anyadi, Patrick; Stephens, Louise; Thomas, Suzanne L.; Reid, Holly; Higgins, Lucy E.; Warrander, Lynne K.; Johnstone, Edward D.; Heazell, Alexander E. P.
Abstract: Introduction: Continuous fetal monitoring is used to objectively record the fetal heart rate and fetal activity over an extended period of time; however, its feasibility and acceptability to women is currently unknown. The study addressed the hypothesis that continuous fetal monitoring is feasible and acceptable to pregnant women. Material and methods: Pregnant participants (n = 22) were monitored using a continuous fetal electrocardiography device, the Monica AN24. Signal quality, duration of recording and cardiotocography findings were correlated with maternal and fetal factors. Participants' change in anxiety before and after monitoring was assessed using validated questionnaires. Participants' experiences were explored through a questionnaire (n = 20) and semi‐structured interview (n = 13). Results: Recordings were successfully obtained in 19 of the 22 participants (86.3%). The mean recording quality of fetal heart rate was 69.0% (range 17.4%‐99.4%) and maternal heart rate was 99.0% (90.9%‐100.0%). Recording quality was positively correlated with gestational age ( P  = 0.05) and negatively correlated with uterine activity and maternal movement ( P  < 0.001). Overall, participants were satisfied with their experience of continuous fetal monitoring; 30% considered it preferable to intermittent monitoring. Continuous fetal monitoring did not significantly increase maternal anxiety, with a trend towards a reduction in Pregnancy Specific Anxiety score ( P  = 0.07). Qualitative analysis grouped women's responses into three themes: (a) reassurance and anxiety, (b) the physical device and (c) future developments in continuous fetal monitoring. Conclusions: Continuous fetal monitoring is a feasible and acceptable form of monitoring to pregnant women although further practical improvements could be incorporated. Further research is required to assess the ability of continuous fetal monitoring to detect fetal compromise.